2021
DOI: 10.12688/f1000research.53931.1
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported COVID-19 among physicians: An Egyptian online study during the pandemic

Abstract: Background: COVID-19 causes a critical occupational risk to frontline healthcare workers (HCWs) who respond to the pandemic, as they are placed in environments with an increased risk of infection exposure. It is a public health priority to understand how transmission occurs to protect this vulnerable group of HCWs. This study was conducted to estimate the incidence of self-reported COVID-19 infection among physicians and its possible associated factors. Methods: An online national survey using Survey Monkey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In Egypt, studies have shown that most of the infected HCWs are nurses and physicians ( Abou-ElWafa et al, 2021 ; El-Sokkary et al, 2021 ; Mostafa et al, 2021 ). This could be due to work overload, extended use/re-use, or suboptimal use of personal protective equipment (PPE), and the transmission of the virus from a HCW to another.…”
Section: Healthcare Workersmentioning
confidence: 99%
See 3 more Smart Citations
“…In Egypt, studies have shown that most of the infected HCWs are nurses and physicians ( Abou-ElWafa et al, 2021 ; El-Sokkary et al, 2021 ; Mostafa et al, 2021 ). This could be due to work overload, extended use/re-use, or suboptimal use of personal protective equipment (PPE), and the transmission of the virus from a HCW to another.…”
Section: Healthcare Workersmentioning
confidence: 99%
“…This could be due to work overload, extended use/re-use, or suboptimal use of personal protective equipment (PPE), and the transmission of the virus from a HCW to another. Environmental factors can also play a role, such as hospital air, devices, and surfaces contaminated by infectious aerosols ( Abou-ElWafa et al, 2021 ). One study conducted by Musa et al compared the prevalence of SARS-CoV-2 infection in HCW in different hospital departments and found that those working in emergency medicine or gastroenterology have higher rates of infection compared to those in other departments including oncology and pediatrics.…”
Section: Healthcare Workersmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Worldwide, the reported prevalence of SARS-CoV-2 infection among health care workers varies widely. [3][4][5][6][7][8] Numerous factors influence these estimates, including methods of ascertaining SARS-CoV-2 infection, access to personal protective equipment and the regional and community prevalence of SARS-CoV-2. In a systematic review of studies published in 2020, the estimated prevalence of laboratory-confirmed SARS-CoV-2 infection in health care workers was 11% (95% confidence interval [CI] 7%-15%).…”
mentioning
confidence: 99%